Co-inhibitory Receptor Signaling in T-Cell-Mediated Autoimmune Glomerulonephritis - Nagai, Kei (Frontiers in Medicine, 2020)
Autoimmune glomerulonephritis occurs as a consequence of autoantibodies and T-cell effector functions that target auto-antigens. Co-signaling through cell surface receptors profoundly influences the optimal activation of T cells. The scope of this review is signaling mechanisms and the functional roles of representative T cell co-inhibitory receptors in the regulation of autoimmune glomerulonephritis, along with current therapeutic challenges mainly on preclinical trials. Co-inhibitory receptors utilize both shared and unique signaling pathway, suggesting specialized functions that provide the rationale behind therapies for autoimmune glomerulonephritis by targeting these inhibitory receptors. These receptors largely suppress Th1 immunity, modify Th17 and Th2 immune response, and enhance Treg function. Anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA4) immunoglobulin (-Ig), which is able to block both activating CD28 and inhibitory CTLA4 signaling, has been shown in preclinical and clinical investigations to have effects on glomerular disease. Other inhibitory receptors for treating glomerulonephritis have not been clinically tested, and efficacy of manipulating these pathways requires further preclinical investigation. While immune checkpoint inhibition using anti-CTLA4 antibodies and anti-programmed cell death 1 (PD-1)/PD-L1 antibodies has been approved for the treatment of several cancers, blockade of CTLA4 and PD-1/PD-L1 are associated with adverse effects that resemble autoimmune disorders, including systemic vasculitis. A renal autoimmune vasculitis model features an initial Th17-dominant lesion followed later by a Th1-dominant outcome and Treg cells that attenuate auto-reactive T-cell function. Towards the development of effective therapies for T-cell mediated autoimmune glomerulonephritis, it would be preferable to pay attention to the impact of the inhibitory pathways in immunological renal disease settings.